Successful rearing of Bactrocera dorsalis on a semi-solid artificial diet - KAUR, SIMRANPREET; SINGH, SANDEEP; MOHANPURIA, PRASHANT; LI, ZHIHONG (The Indian Journal of Agricultural Sciences, 2021)
The fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) is an economically important polyphagous pest and has been adjudged as one of the five most devastating fruit flies throughout the world. These flies are highly polyphagous, multivoltine, fertile, and mobile which makes it very difficult to manage these insect-pests. Finding a simple, cheap, and appropriate rearing approach of B. dorsalis is an urgent need to support research activities for management of this pest. This investigation is meant to evaluate various artificial diets and to find out the most suitable artificial diet for mass rearing of this pest. In the present studies, five different artificial diets were used for the rearing of B. dorsalis at Punjab Agricultural University, Ludhiana during 2018–19. A semi-solid artificial diet consisting of 1000 ml water, 40 g dry yeast, 120 g sucrose, 1 g sorbic acid, 6.6 g ascorbic acid, 10 g agar, 10 g soya peptone, 0.1 g ampicillin, and 0.03 g tetracycline was considered most suitable for successful rearing of B. dorsalis. The biological parameters of B. dorsalis were used to validate the diet quality and rearing procedure. This diet supported the development of B. dorsalis efficiently and was used further for evaluation of RNA interference (RNAi) studies. This artificial diet and suggested rearing procedure will help to maintain culture of B. dorsalis and further help to study biology and management of other insect-pests species as well.